A Development of a Problem-Based Learning Model to Improve Civics Learning Outcomes of Fifth Grade Students - Eva Pasaribu; Esti Marlina Sirait (International Journal of Contemporary Studies in Education (IJ-CSE), 2025)
Purpose – This study was conducted based on the importance of maintaining educational quality in achieving the vision of Indonesia Emas 2045. The learning process in Civics education still lacks the implementation of cooperative and varied learning models, resulting in low student learning outcomes. Therefore, this study aimed to develop a Problem-Based Learning (PBL) model to improve the Civics learning outcomes of fifth-grade students.Methodology – This study employed a Research and Development (R&D) approach using the Dick and Carey instructional development model. The research was conducted longitudinally through several stages, including needs analysis, design, development, implementation, and evaluation. The subjects of this study were fifth-grade students at UPTD SD Negeri 124387. Data were collected using observation, questionnaires, interviews, and learning outcome tests. The developed learning products included teaching materials, PowerPoint presentations, animated videos, and practice exercises.Findings – The results showed that the developed Problem-Based Learning model was feasible and effective in improving students’ Civics learning outcomes. Students became more active, collaborative, and engaged in the learning process. The implementation of interactive learning media also increased students’ motivation and understanding of learning materials.Novelty – The originality of this study lies in the integration of the Problem-Based Learning model with various interactive learning products to create active, student-centered, and technology-supported Civics learning in elementary schools.Significance – This study is beneficial for teachers, students, schools, and researchers as a reference for developing innovative Civics learning models that can improve learning quality and student outcomes in elementary education